Barriers and facilitators to supporting women with postnatal depression and anxiety: A qualitative study of maternal and child health nurses' experiences. Issue 3 (14th February 2022) - Arefadib, Noushin; Shafiei, Touran; Cooklin, Amanda
Abstract: Aims and objectives: To explore maternal and child health nurses' experiences of supporting women with postnatal depression and anxiety and the factors which impact these. Background: Maternal and child health nurses play a key role in identifying women with postnatal depression and anxiety and facilitating their access to appropriate supports. Understanding how nurses carryout this work, and the conditions which impact their ability to do so, is critical to the development of service delivery frameworks that can facilitate optimal outcomes for women and their families. Despite this, little is known about this subject. Design: A qualitative descriptive study. Methods: Participants were maternal and child health nurses practicing for at least six months and regularly seeing new mothers in Victoria, Australia. Twelve nurses were interviewed. Thematic analysis was conducted to identify patterns across our data. Qualitative content analysis was used to identify issues which were most emphasised by nurses. Reporting complies with the COREQ checklist. Findings: Three overarching themes were identified. Theme one pertained to steps taken by nurses following the identification of depression or anxiety symptoms and the shared challenges they encountered. Theme two concerned nurses' experiences of supporting women who required acute mental health interventions and the systemic barriers they faced. Finally, theme three related to how the existing service delivery model could be improved to better support nurses in their work. Conclusions: The complex system within which nurses operate presents barriers that can impede their ability to respond to women with postnatal mental health issues. There is a need for service delivery frameworks that better support nurses and facilitates equitable access to mental healthcare. Relevance to clinical practice: Facilitating equitable access to all perinatal mental health services and interventions must be at the heart of all future policy, funding and service delivery frameworks.